2018
DOI: 10.1016/j.buildenv.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to climate change adaptation in the Australian construction industry – Impetus for regulatory reform

Abstract: It is increasingly recognised that the risks associated with climate change must be addressed through both mitigation and adaptation. Buildings are vulnerable to climate change risk and are also the source of a significant proportion of greenhouse gas emissions which contribute to climate change. The construction industry has significant potential to facilitate adaptation through actions that both reduce its contribution to greenhouse gas emissions across the construction and building lifecycle, and through ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Galvin [16]'s and Guest [17]'s studies indicated that 12 interviews could be considered adequate for the qualitative approach while 20 and 15±10 are the figures for the appropriate number of interviews stated by Crouch and McKenzie [18] and Kvale and Brinkmann [19], respectively. Also, similar sample sizes with this study were also found out in previous publications in the construction area such as Hurlimann [20]'s and Sacilotto and Loosemore [21]'s studies. Regarding the sampling methods, the purposive sampling was initially utilized with criteria including the number of years working in the industry, at least five year's experience, and participating in a number of BIM projects before adopting the snowball sampling used to determine the BIM experts in the New Zealand construction industry.…”
Section: Methodssupporting
confidence: 88%
“…Galvin [16]'s and Guest [17]'s studies indicated that 12 interviews could be considered adequate for the qualitative approach while 20 and 15±10 are the figures for the appropriate number of interviews stated by Crouch and McKenzie [18] and Kvale and Brinkmann [19], respectively. Also, similar sample sizes with this study were also found out in previous publications in the construction area such as Hurlimann [20]'s and Sacilotto and Loosemore [21]'s studies. Regarding the sampling methods, the purposive sampling was initially utilized with criteria including the number of years working in the industry, at least five year's experience, and participating in a number of BIM projects before adopting the snowball sampling used to determine the BIM experts in the New Zealand construction industry.…”
Section: Methodssupporting
confidence: 88%
“…Researchers have developed several kinds of approaches to understand and address climate change adaptation barriers including semistructured surveys, meta‐analyses, and multiphase frameworks (Aguiar et al., ; Aronsson & Schöb, ; Enríquez‐de‐Salamanca et al., ; Hurlimann, Browne, Warren‐Myers, & Francis, ; Khanal, Wilson, Hoang, & Lee, ; Moser, Ekstrom, & Kasperson, ; Ng & Ren, ; Ray, Hughes, Konisky, & Kaylor, ). Of these, Moser et al.’s () three‐phase framework provides a roadmap to assess key socioecological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Building stock owners and professionals in the UK were surveyed, and the findings were analyzed to improve their understanding of climate change risks and the impacts on their assets. Furthermore, Hurlimann et al [78] investigate barriers to climate change adaptation. Buildings contribute to greenhouse gas emissions and are vulnerable to climate change, which makes development in this field significant.…”
Section: Policymentioning
confidence: 99%